Leopard (Panthera pardus) occupancy in the Chure range of Nepal - Lamichhane, Babu Ram; Lamichhane, Saneer; Regmi, Rajan; Dhungana, Milan; Thapa, Shyam Kumar; Prasai, Anil; Gurung, Aashish; Bhattarai, Santosh; Paudel, Rajan Prasad; Subedi, Naresh (Dryad, 2021)
Conservation of large carnivores like leopards requires large and
interconnected habitats. Despite the wide geographic range of the leopard
globally, only 17% of their habitat is within protected areas. Leopards
are widely distributed in Nepal but their population status and occupancy
is poorly understood. We carried out the sign-based leopard occupancy
survey across the entire Chure range (~19,000 km2)to understand the
habitat occupancy along with the covariates affecting their occupancy.
Leopard signs were obtained from in 70 out of 223 grids surveyed, with a
naïve leopard occupancy of 0.31. The model-averaged leopard occupancy was
estimated to be 0.5732 (SE 0.0082) with a replication level detection
probability of 0.2554 (SE 0.1142). The top model shows the additive effect
of wild boar, ruggedness, presence of livestock and human population
density positively affecting the leopard occupancy. The detection
probability of leopard was higher outside the protected areas, less in the
high NDVI (normalized difference vegetation index) areas, and higher in
the areas with livestock presence. Presence of wild boar was strong
predictor of leopard occupancy followed by presence of livestock,
ruggedness and human population density. Leopard occupancy was higher in
west Chure (0.70±SE 0.047) having five protected areas compared to east
Chure (0.46 ±SE0.043) with no protected areas. Protected areas and prey
species had positive influence on leopard occupancy in west Chure range.
Similarly in the east Chure, the leopard occupancy increased with prey,
NDVI, and terrain ruggedness. Enhanced law enforcement and mass awareness
activities are necessary to reduce poaching/killing of wild ungulates and
leopards in the Chure range to increase leopard occupancy. In addition,
maintaining the sufficient natural prey base can contribute to minimize
the livestock depredation and hence, decrease the human-leopard conflict
in the Chure range.
The study area was divided into blocks, grids, and sub grids (Chure range,
19000 km2) (details in the paper). Each grid was 10 km x 10 km in size.
Furthermore, each grid was subdivided into 16 sub-grids, each measuring 2
km by 2 km. The presence and absence of leopards within each sub-grid were
collected. The leopard's occupancy was estimated using the software
PRESENCE (details in the paper).
Due to logistical constraints, the survey effort across the grids varies
due to the rough terrain of the Chure range. As a result, we were unable
to survey all of the sub-grids in the Chure range. In the datasheet, these
missing sub-grids are referred to as 'null,' i.e. 1= leopard
presence, 0= leopard absence, null= unsurveyed grids.